Ethic and bioethic dilemmas on palliative care for hospitalized elderly: nurses' experience - Juliana Bezerra do Amaral; Maria do Rosário de Menezes; Maria Antonia Martorell-Poveda; Simone Cardoso Passos (Universidad de Alicante, 2012)
Objective: analyzing ethic and bioethics dilemmas experienced by nurses who take palliative care for hospitalized elderly. Method: quality study, exploring, descriptive, using the interview as technical for collecting oral history from tem nurses. The context was a geriatric palliative care unit from the city of Salvador - Brazil, in the period between May and August 2005. Content was used for speech analyzing. Results: the speeches arose dilemmas like: artificially prolonging of life; feeding terminal condition patients; neglecting information; and obtaining an undesired effect - Double effect. Conclusion: the nurses experienced some ethic and bioethics dilemmas, values conflicts and contradictions, for it is impossible to dissociate the historical and cultural aspects inserted in the daily life of the Health Professionals. However, the theoretical study about this theme Will contribute to complete deployment of the basics of palliative care by enabling cultural point of view transformation concerning to the process of dying and death.